Interference of phototherapy with blue LED light on the behaviour of mice infected with Toxoplasma gondii - Marina Monteiro de Castro Burle; Ben-Hur Araújo Batista da Silva; Débora Nonato Miranda de Toledo; Lauro de Assis Duarte Junior; Rodrigo Fernando Bianchi; Érica S. Martins-Duarte; André Talvani; Cristiano Schetini de Azevedo (PLoS ONE, 2026)
Toxoplasma gondii is an intracellular protozoan capable of promoting physiological and behavioural changes in hosts. When female mammals acquire T. gondii for the first time during pregnancy, Congenital Toxoplasmosis (CT) can occur, posing a significant risk to the foetus. Due to challenges in diagnosing and treating CT, a new blue LED light therapy (BLLT) was proposed to eliminate parasites during placenta and tissue invasion in mice; however, its effects on the behaviour of the animals are unknown. Thus, behavioural analysis was carried out in pregnant infected Swiss mice under BLLT (applied continuously for 12 hours, from 7 am to 7 pm, maintaining an intensity of 460 nm and 7 μW/cm²). Infected mice, regardless of light exposure, exhibited increased inactivity and reduced maintenance behaviours. BLLT influenced certain behaviours, such as an increase in abnormal behaviours in infected mice and higher food and water intake in non-infected mice, suggesting a potential stress effect. Grooming decreased under BLLT in infected mice, while affiliative interactions were reduced in non-infected mice under conventional light. Activity levels were largely unaffected in infected mice, but blue light exposure increased activity in non-infected mice. While our study highlights the potential of BLLT to reduce parasite load, further research is needed to investigate the long-term behavioural and physiological effects, as well as to clarify the mechanisms involved. In conclusion, BLLT may mitigate parasite load and influence behavioural outcomes, while prolonged exposure can act as a stressor, moderately affecting welfare. Future research should explore optimized light regimens, integrate physiological and behavioural measures, and evaluate long-term effects to balance therapeutic efficacy and animal welfare.